“On the Road to A Better Life”: An Innovative Suicide Prevention Program Based on The Realization of Meaningful Personal Goals - Lapierre, Sylvie; Desjardins, Sophie; Dube, Micheline; Marcoux, Lyson; Miquelon, Paule; Boyer, Richard (Journal of Depression And Therapy, 2017)
Background. Suicide prevention programs centred on reinforcing protective factors are uncommon. Aims. Since leading a meaningful life is incompatible with suicide, a 14-week program designed to help participants realize meaningful personal goals was created to improve the psychological well-being (PWB) of depressed older adults (≥ 65 years). Method. Persons scoring 9 or above on the Beck Depression Inventory- II (M = 22.05) took part in the program (n = 24). Their levels of PWB, depression, and suicidal thoughts were compared to those of a control group (n = 18). The questionnaires were completed three times: pre-test, post-test, and follow-up (six months later). Results. Analyses showed that the program participants improved significantly on most indicators of wellbeing, including suicidal ideation, indicating that increasing protective factors could be an innovative way to prevent suicidal ideation. However, the changes were not significantly higher than those observed in the control group, except for meaning in life. Conclusions. The absence of difference between groups was partly justified by unexplained improvements of controls between post-test and follow-up. Future studies should develop suicide prevention program thatincrease protective factors that provide individuals with means to achieve an optimal state of functioning.
Keywords: protective factors; suicidal ideation; intervention program; older adults; meaning in life; depression; mental health promotion; personal goals.